THE EFFECT OF CELEBRITY ENDORSSEMENT, ONLINE CUSTOMER REVIEW AND CUSTOMER EXPERIENCE ON PURCHASE INTENTION MARKETPLACE SHOPEE (Study on Students at Stikubank University (Unisbank) Semarang) - Roy Andhika Oktaviansyah; Mulyo Budi Setiawan (SEAN Institute, 2022)
This research measures the Influence of Trust, Corporate Image, and Price Perception on Purchasing Decisions. This research was conducted on active students of Stikubank Semarang. Sampling technique on respondents by applying purposive sampling technique, using the following criteria: Active students at Stikubank University (Unisbank) Semarang who have made purchases at the Shopee Marketplace. The method of unification of data uses questionnaires that have been tested for validity and reliability. Data analysis in this study used multiple linear regression analysis. The results showed that Trust, Corporate Image and Price Perception have a positive and significant influence on Purchasing Decisions.